Upaya Meningkatkan Konsentrasi Anak Usia 5-6 Tahun Melalui Metode Pembelajaran Berbasis Proyek di TK Tunas Bangsa XIII Koto Kampar - Febi Astri Nur Sinaga; Musnar Indra Daulay; Yenda Puspita (Journal of Innovation in Teaching and Instructional Media, 2026)
Learning concentration is an important aspect that plays a role in supporting the success of early childhood in participating in the learning process. However, in reality, many children still have difficulty maintaining focus, which impacts their developmental achievements. One effort that can be made to overcome this problem is through the application of the Project-Based Learning (PjBL) method which emphasizes the active involvement of children in learning activities. This research is a Classroom Action Research (CAR) carried out in two cycles, each including the planning, implementation, observation, and reflection stages. The research subjects were 15 group B children aged 5–6 years at Tunas Bangsa XIII Koto Kampar Kindergarten, consisting of 7 boys and 8 girls. Data collection techniques used observation, documentation, and structured interviews, with qualitative and quantitative data analysis. The results of the study showed a significant increase in children's learning concentration, from an average of 14.4% in the pre-cycle, increasing to 32.3% in cycle I, and reaching 90.4% in cycle II. Thus, the application of the PjBL method has been proven effective in improving the learning concentration of early childhood.